Our initial learning curve in the enzymatic debridement of severely burned hands—Management and pit falls of initial treatments and our development of a post debridement wound treatment algorithm. Issue 2 (March 2017) - Schulz, A.; Perbix, W.; Shoham, Y.; Daali, S.; Charalampaki, C.; Fuchs, P.C.; Schiefer, J.
Highlights: Promising results for enzymatic debridement of deep burned hands with NexoBrid™. Long term spontaneous healing offers good scar quality. Healing process was accelerated by the preservation of viable dermis and its epithelialization. Time efficient treatment and early rehabilitation. Plexus anaesthesia enables a sufficient and flexible pain management. Abstract: Introduction: Excisional surgical debridement (SD) is still the gold standard in the treatment of deeply burned hands, though the intricate anatomy is easily damaged. Previous studies demonstrated that enzymatic debridement with the bromelain debriding agent NexoBrid ® (EDNX) is more selective and thus can preserve viable tissue with excellent outcome results. So far no method paper has been published presenting different treatment algorithms in this new field. Therefore our aim was to close this gap by presenting our detailed learning curve in EDNX of deeply burned hands. Methods: We conducted a single-center prospective observational clinical trial treating 20 patients with deeply burned hands with EDNX. Different anaesthetic procedures, debridement and wound treatment algorithms were compared and main pitfalls described. Results: EDNX was efficient in 90% of the treatments though correct wound bed evaluation was challenging and found unusual compared to SD. Post EDNX surprisingly the majority of the burn surface area was found overestimated (18 wounds). Finally we simplified our process and reduced treatment costs by following a modified treatment algorithm and treating under plexus anaesthesia bedside through a single nurse and one burn surgeon solely. Suprathel ® could be shown to be an appropriate dressing for wound treatment after EDNX. Complete healing (less 5% rest defect) was achieved at an average of day 28. Conclusion: EDNX in deep burned hands is promising regarding handling and duration of the treatment, efficiency and selectivity of debridement, healing potential and early rehabilitation. Following our treatment algorithm EDNX can be performed easily and even without special knowledge in burn wound depth evaluation.